2002
DOI: 10.1074/jbc.m208449200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Translocation of Fluorescent Precursor Proteins into Escherichia coli Membrane Vesicles

Abstract: Protein secretion in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 31 publications
3
50
1
Order By: Relevance
“…The conditions employed in the in vitro assays represent multiple turnovers of the translocase (22). The experimental data show that 4 molecules of proOmpA-P1 (in a total of 1388 amino acids) are translocated in the same time as 1 molecule of proOmpA-P8 (in a total of 1397 amino acids).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The conditions employed in the in vitro assays represent multiple turnovers of the translocase (22). The experimental data show that 4 molecules of proOmpA-P1 (in a total of 1388 amino acids) are translocated in the same time as 1 molecule of proOmpA-P8 (in a total of 1397 amino acids).…”
Section: Discussionmentioning
confidence: 75%
“…tease protection assay followed by direct fluorescent detection in the gel (22). Quantitative analysis of the labeling efficiency indicated that all proOmpA derivatives were equally labeled with fluorescein maleimide, with an efficiency of ϳ45%.…”
Section: Construction and Purification Of Proompa Derivatives With Mumentioning
confidence: 99%
See 2 more Smart Citations
“…Association of SecA with the SecYEG translocon (26,30) promotes ADP release, and this step is closely coupled to translocation of precursor proteins (37,38). From kinetic data using MANT-ADP, it is evident that SecA2 releases ADP much more slowly than SecA1; consequently, the affinity of SecA2 for ADP is much higher than SecA1.…”
Section: Discussionmentioning
confidence: 97%